ANTARA SANKSI ADAT DAN KETENTUAN MASA IDDAH DALAM PERKAWINAN PRESPEKTIF URF (STUDI KASUS KOTA NOPAN KABUPATEN MANDAILING NATAL - Lubis, Sukron; Nasution, Muhammad Mahmud (JAS : Jurnal Ahwal Syakhshiyyah, 2024)
Sharia-regulated marriage to reconcile men and women and legitimise women in men's presence. Marriage may defend humanity and prevent religious doctrine abuses. Marriage during iddah is significant to experts. The iddah time is necessary for marriage validity, hence the result could nullify the marriage. This research uses Empirical Legal Research, or field research, which relies on interview and observation data. Legislation is empirically studied as structured behaviour in social interactions and relationships. Couples who violate customs must live by ancestral rules, which include being confronted in the traditional house with families from both sides, being tried by the village chief, hatobangon, and harajaon, being questioned about the husband's consent after marriage, facing sanctions, apologising for the violation, formalising the marriage, and possibly being expelled from the village.Despite family pressure, arranging marriages is a fasid norm since it breaches Islamic law, especially during the iddah time. Qanun Number 9 of 2008 on the Development of Customary Life and Customs in Aceh calls expulsion from the village urf shahih because it deters, prevents dishonour, and creates a safe atmosphere